Electric shock–induced cardiac injuries requiring surgical intervention: Case series and a brief review. Issue 2 (28th November 2019) - Jacob, Samuel; Landolfo, Kevin P.; El‐Sayed Ahmed, Magdy M.; Thomas, Mathew; Makey, Ian A.; Pham, Si M.
Abstract: Background: Electric shock–induced cardiac injuries, such as myocardial infarction, thrombosis, and dissection, are rare. Few cases have been previously reported. The right coronary artery is most often affected because of its proximity to the chest wall. Aims: To study the extend of electrical injuries on cardiac tissues and its surgical management. Materials and Methods: We conducted a retrospective study on our patients in the last five years, looking for cardiac electrical injuries treated surgically in our department, we identified three cases. Result: Our three‐case series, reported herein, showed that multiple cardiac tissues are susceptible to electrical injuries, specifically the left coronary artery, inferior vena cava, and right ventricular free wall. In our series, the first patient was a 32‐year‐old man with triple vessel thrombosis and dissection who survived the electric shock. The second patient was a 23‐year‐old man who had an inferior vena cava burn and bruising; his heart was used for transplantation. After the transplant, the recipient had a left coronary artery dissection and underwent coronary artery bypass grafting. The third patient was a 30‐year‐old man (potential heart donor) who had a hematoma of the right ventricular free wall, possible coronary artery dissection, inferior vena cava bruising, and tissue damage. His heart was not used for transplant because of quality concerns. Conclusion: We recommend that any person who sustains high voltage (500 V or more) electric shock should be evaluated carefully in the emergency department, including with echocardiography and cardiac catheterization, if indicated, to determine the extent of the injury and the viability of the heart, for patients who do not survive as a donor organ.